Dikesrensning och skyddsdikning - Elm, David (2008)
During the 20th century a significant proportion (about 15 %) of the peat-covered wetlands in Sweden were drained to improve forest productivity. Area wise, most of the forest drainage was done in northern Sweden, but relatively speaking a larger part of the wetlands have been drained in the southern parts of the country. Most often, the forest drainage resulted in increased forest growth, but failures were not unusual, and harmful effects, e.g. on species richness, have been a common cause for draining. Ditch cleaning is necessary for maintaining the ditches in good condition. Ditches in sensitive environments, and ditches in stands where the drainage did not give the intended effect should however not be maintained. Instead such areas could be set aside for nature conservation.